HYDROTHERMAL OLIVINE IN IRON DEPOSITS OF ANGARA-ILIM TYPE (SIBERIAN CRATON) - Polozov A.G.; Vorontsov A.Y.; Piskunova L.F.; Sapozhnikov A.N.; Matveyeva L.N. (My University, 1990)
Although olivine is commonly formed in metamorphic and metasomatic processes, cases of its crystallization from hydrothermal solutions are extremely rare. In these cases the hydrothermal nature of the olivine is inferred from its occurrence in veins in ultramafic plutons. In iron deposits of Angara-Ilim type (on the Siberian craton), formed as a result of the conjunction in space of at least three stages (epochs) of mineragenesis, olivine has been found in druses formed during the last, or hydrothermal, haloidsulfate stage, genetically associated with the discharge of brines from the Lower Paleozoic deposits of the sedimentary cover on the Siberian craton in these structures. For the first time under natural conditions, olivine has been found to have crystallized from hydrothermal solutions in a free space. Its distinctive crystallographic feature, like that of hydrothermal olivines, whether natural or grown experimentally, is flattening on the (110) face, and a geochemical feature consists of its lower concentrations of Ni and Go than in olivines of other genetic types. Under the conditions of ore deposits of Angara-Ilim type, retention of olivine may be fastened by its incorporation and preservation by late mineral phases - calcite and halite. When halite is dissolved by meteoric waters, olivine is serpentinized, leading to its disappearance from the upper levels of ore deposits.
Keywords: Paleozoic; Paleozoic; Палеозой